Varying wall temperature and thermal radiation effects on MHD boundary layer liquid flow containing gyrotactic microorganisms - Sankad G.; Ishwar M.; Dhange M. (Partial Differential Equations in Applied Mathematics, 2021)
Nanofluid dynamics and magnetohydrodynamics have tremendously contributed to industrial applications. The presence of nanoparticles in base fluids enhances the specific chemical and physical properties. This study intends to examine the combined impacts of magnetic field and convective boundary state on bioconvection of a Casson fluid and concentration of nanoparticles in presence of gyrotactic microorganisms over a straight extending sheet. To simplify the governing equations comprising momentums, temperature, and concentration of nanoparticles, and microorganisms, the similarity transformations are employed. Emerged system of coupled nonlinear differential equations is solved by the differential transformation method and MATHEMATICA software. The impacts of the Brownian motion parameter, thermophoresis parameter, Casson fluid parameter, radiation parameter, suction or mass flux parameter, magnetic field, Prandtl number, Lewis number, Peclet number, and bioconvection parameter on dimensionless velocity, temperature, nanoparticles concentration, and microorganisms density profile are interpreted through graphs. The present bioconvection analysis is most relevant to the study of bioproducts.